2007
DOI: 10.1021/es071324r
|View full text |Cite
|
Sign up to set email alerts
|

Artificial UV-B and Solar Radiation Reduce in Vitro Infectivity of the Human Pathogen Cryptosporidium parvum

Abstract: The potential for solar ultraviolet (UV) radiation to act as a significant abiotic control of Cryptosporidium parvum oocysts in nature is unknown. Infectivity of C. parvum following exposure to artificial UV-B and natural solar radiation, with and without UV wavelengths, was tested under controlled pH and temperature conditions. Percent infectivity of exposed oocysts was determined by in vitro cell culture. Artificial UV-B exposures of 32 and 66 kJ/m2 significantly decreased oocyst infectivity by an average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 38 publications
7
39
0
Order By: Relevance
“…1). These data support the observations of others that solar radiation reduces oocyst infectivity (6,11,15); however, approximately 20% of the oocysts exposed to the highest levels of solar radiation remained infectious and a potential public health threat.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…1). These data support the observations of others that solar radiation reduces oocyst infectivity (6,11,15); however, approximately 20% of the oocysts exposed to the highest levels of solar radiation remained infectious and a potential public health threat.…”
supporting
confidence: 89%
“…Despite various lengths of exposure time (90, 50, and 60 min for the July 9, July 15, and August 25 experiments, respectively), sky conditions resulted in all three experiments having similar solar exposure (0.37, 0.28, and 0.23 exposure days, respectively) ( Table 1), and these exposures were comparable to those in previous experiments (6) (0.33 to 0.38 exposure days), in which infectivity was reduced to 0 to 6% of the stock infectivity (compared to 16 to 20% in these experiments). Differences in infectivity reductions may result from the greater attenuation of radiation by the glass-covered flow chambers used here compared to the quartz dishes used previously (6), variation in oocyst lots (26), and overnight oocyst storage before infectivity processing (6).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Artificial UV radiation has also been used to sterilize drinking water supplies by inactivating pathogens (WOLFE, 1990) and degrading pollutants (LEGRINI et al, 1993). Natural solar UV radiation can also significantly reduce the infectivity of pathogens like Cryptosporidium parvum (CONNELLY et al, 2007) as well as degrade contaminants such as PAHs (LEE, 2003). DOM can reduce phototoxicity by selectively absorbing UV (BARRON et al, 2000;DIA-MOND et al, 2000) or by binding toxic compounds (ORIS et al, 1990;WEINSTEIN and ORIS, 1999).…”
Section: Uv Contaminant Toxicity and Nutrient Cyclingmentioning
confidence: 99%
“…Male-specific-2 bacteriophage (MS2) has been used as a model organism for Cryptosporidium, Giardia, and intestinal viruses to test the inactivation by UV-C (Havelaar et al, 1993;US EPA 2006). Although a few studies have reported the use of sunlight (Connelly et al, 2007;Kohn and Nelson 2007;King et al, 2008;Gomez-Couso et al, 2009), most UV disinfection studies have used a low-or medium-pressure mercury lamp at a wavelength of around 254 nm (near the peak wavelength of DNA absorbance: UV-C range).…”
Section: Introductionmentioning
confidence: 99%